IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PANCASILA MATERI AKU MENEGENAL INDONESIA - Rebong, Rosa Ero; Rozhana , Kardiana Metha; Chotimah, Chusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning outcomes in Pancasila education on the topic “Aku Mengenal Indonesia” through the implementation of the Problem Based Learning (PBL) model. The study was motivated by the low learning outcomes of first-grade students, where only 55.56% of students achieved the minimum mastery criteria (KKM) during the initial observation. This research used Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 28 first-grade students of SDN Merjosari 1 Malang. Data were collected through tests, observations, interviews, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results showed that the implementation of the Problem Based Learning (PBL) model improved students’ learning outcomes. Mastery learning increased from 64% to 75% in cycle I and improved significantly from 82% to 93% in cycle II with an average score of 80. These findings indicate that the Problem Based Learning model effectively improves students’ learning outcomes and participation in Pancasila learning.